2007
DOI: 10.1002/ijc.22573
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Dyrk1a in HPV16 immortalized Keratinocytes enable evasion of apoptosis

Abstract: Immortalization is a critical event in virus-related oncogenesis. No enough information, however, is currently available to elucidate the changes that occur in cellular molecules during immortalization. To identify potential cellular markers or regulators involving in immortalization, a paired-cell model of primary foreskin keratinocytes (FK) and HPV16 immortalized foreskin keratinocytes were established. Using mRNA differential display, RT-PCR and Northern blot methods, we have identified and confirmed that D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…The first evidence for the possible involvement of DYRK1A in tumorigenesis was the observation that DYRK1A is highly expressed in HPV16 immortalized keratinocytes and malignant cervical lesions compared with their primary foreskin keratinocytes and normal cervical tissues, respectively. 28 In line with this result is the finding that knockdown of endogenous DYRK1A in HPV16 immortalized keratinocytes leads to apoptosis, 28 suggesting that DYRK1A may act as a cell survival and anti-apoptotic molecule in cells. Consistent with this notion, DYRK1A appears to utilize several different mechanisms to inhibit apoptosis and to promote cell proliferation.…”
Section: The P53-mir-1246-dyrk1a-nfatmentioning
confidence: 88%
See 1 more Smart Citation
“…The first evidence for the possible involvement of DYRK1A in tumorigenesis was the observation that DYRK1A is highly expressed in HPV16 immortalized keratinocytes and malignant cervical lesions compared with their primary foreskin keratinocytes and normal cervical tissues, respectively. 28 In line with this result is the finding that knockdown of endogenous DYRK1A in HPV16 immortalized keratinocytes leads to apoptosis, 28 suggesting that DYRK1A may act as a cell survival and anti-apoptotic molecule in cells. Consistent with this notion, DYRK1A appears to utilize several different mechanisms to inhibit apoptosis and to promote cell proliferation.…”
Section: The P53-mir-1246-dyrk1a-nfatmentioning
confidence: 88%
“…Since DYRK1A is highly expressed in Down syndrome patients due to trisomy 21 and is shown to promote cell survival and to inhibit apoptosis, 26,28,[31][32][33][34] it would be predicted that these patients might have the high risk of developing cancer. However, the story might not be this simple, as some Down syndrome-associated proteins were also found to induce apoptosis in cells, such as ETS2.…”
Section: Role Of the P53-mir-1246-dyrk1a-nfat Pathway In Down Syndromementioning
confidence: 99%
“…It is unclear why E1A targets Dyrk1A and -1B, but the interaction with E1A stimulates their kinase activity in vitro and their binding overlaps the CtBP binding site (148). In an interesting parallel, the immortalization of keratinocytes by HPV16 E7 results in an increase in Dryk1A expression, and a similar increase in Dyrk1A expression is present in malignant HPV-positive cervical cancers, where it has been proposed to function as an antiapototic factor (15). E1A may utilize Dyrk1A as a survival factor in a manner similar to that of HPV E7, but this remains to be determined.…”
Section: Morfs and Lms In E1amentioning
confidence: 99%
“…DYRK1A expression level is higher in immortalized HPV16-infected keratinocyte cells. DYRK1A disappears when the HPV E7 oncoprotein is silenced, and this leads to increased cell apoptosis [13]. It has been reported that DYRK1A and DYRK3 may be involved in tumorigenesis through a phosphorylation event that activates SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DYRK1A is also present and increased in HPV16 immortalized cells, but not in primary keratinocytes. Transfection of E7 siRNA oligo into immortalized cells leads to diminish E7 expression as well as DYRK1A [13]. Given the clues about miR-1246, we are interested with miR-1246 in cervical cancer development.…”
Section: Introductionmentioning
confidence: 99%